Binder composition for electricity storage device, slurry for electricity storage device electrode, electricity storage device electrode, and electricity storage device

By using a binder composition of a polymer composition and anionic surfactant in a specific ratio, the problems of adhesion and surface indentation of PVDF binder in lithium-ion batteries are solved, the surface state and ion conductivity of the electrode are improved, and the cycle life of the battery is extended.

CN120660202APending Publication Date: 2025-09-16ENEOS MATERIALS CORP
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202480011562.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-02-09
Filing Date
2024-02-07
Publication Date
2025-09-16

AI Technical Summary

Technical Problem

The polyvinylidene fluoride (PVDF) binder used in existing lithium-ion batteries easily forms cross-links under alkaline conditions, resulting in a decrease in adhesion and the formation of dents on the coating surface, affecting the battery yield and performance.

Method used

A polymer composition with a specific proportion, including repeating units such as an aromatic vinyl compound, an unsaturated carboxylic acid ester, an α,β-unsaturated nitrile compound, a compound with a sulfonic acid group, and (meth)acrylamide, is used, together with an anionic surfactant as an emulsifier, to form a stable binder composition for the preparation of lithium-ion battery electrodes.

Benefits of technology

The surface condition, adhesion and ion conductivity of lithium-ion battery electrodes are improved, and the cycle life and charge and discharge characteristics of the battery are extended.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005537493550000281
    Figure BDA0005537493550000281
  • Figure BDA0005537493550000291
    Figure BDA0005537493550000291
  • Figure BDA0005537493550000301
    Figure BDA0005537493550000301
Patent Text Reader

Abstract

Provided is a binder composition for a power storage device, said binder composition being capable of producing a power storage device electrode having excellent surface state, adhesion, and ion conductivity, and being capable of improving the cycle life characteristics of a power storage device. The binder composition for an electricity storage device according to the present invention contains a polymer (A) and an emulsifier (B), the emulsifier (B) being 30-30000 ppm relative to the total mass of the polymer (A), and the emulsifier (B) being 30-30000 ppm relative to the total mass of the polymer (A), the emulsifier (B) being 30-30000 ppm relative to the total mass of the repeating units contained in the polymer (A). The polymer (A) contains 1-50 mass% of a repeating unit (a1) derived from an aromatic vinyl compound and 20-75 mass% of a repeating unit (a2) derived from an unsaturated carboxylic acid ester.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a binder composition for an electrical storage device, a slurry for an electrical storage device electrode, an electrical storage device electrode, and an electrical storage device. Background Art

[0002] In recent years, as a power source for driving electronic devices, a power storage device having high voltage and high energy density is required. As such a power storage device, lithium ion batteries, lithium ion capacitors, etc. are expected.

[0003] The electrodes used in such an electrical storage device are manufactured by applying a composition containing an active material and a polymer functioning as a binder (slurry for electrical storage device electrodes) on the surface of a current collector and drying it. The properties required of a polymer used as a binder include the ability of the active materials to bind to each other and the ability of the active material to adhere to the current collector. In addition, the anti-powdering property, which prevents the fine powder of the active material from falling off from the active material layer when cutting the composition coating obtained by coating and drying (hereinafter also referred to as the "active material layer"), can be mentioned. Such a binder material can provide the electrical storage device with good charge and discharge characteristics by showing good adhesion and reducing the internal resistance of the battery caused by the binder material.

[0004] It should be noted that it is empirically known that the binding ability of the active materials, the adhesion between the active materials and the current collector, and the resistance to powder loss are generally proportional to the performance. Therefore, in this specification, these are sometimes collectively expressed using the term "adhesion".

[0005] Currently, in order to produce electrochemical devices with excellent capacity and charge-discharge cycle characteristics, the use of positive electrode active materials with high reactivity with water is being studied. In addition, polyvinylidene fluoride (PVDF) is the most widely used binder for organic solvent-based storage device electrodes. PVDF has good adhesion and oxidation resistance, but because it contains fluorine atoms, it has a high environmental burden and the instability of raw material supply is becoming increasingly significant (for example, see Patent Document 1).

[0006] Under such circumstances, various binder materials have been proposed to solve various problems of positive electrode slurries (see, for example, Patent Documents 1 and 2).

[0007] Prior art literature

[0008] Patent Literature

[0009] Patent Document 1: Japanese Patent Application Laid-Open No. 10-298386

[0010] Patent Document 2: Japanese Patent Application Publication No. 2019-194944 Summary of the Invention

[0011] However, it is known that in methods using cathode slurries containing conventionally used PVDF or the sulfonated PVDF disclosed in Patent Document 1, crosslinks are formed, particularly under alkaline conditions, along with HF removal. If these crosslinks form in the cathode slurry, adhesion may be impaired. Furthermore, when applying conventionally used cathode slurries, residual emulsifiers and the like in the slurry may cause dents on the surface of the coating film due to bubble breakage. Such surface defects can lead to a decrease in the product yield and require prevention.

[0012] Several aspects of the present invention provide a binder composition for an electrical storage device that can produce an electrical storage device electrode having excellent surface condition, adhesion, and ion conductivity, and can improve the cycle life characteristics of the electrical storage device.

[0013] The present invention has been made to solve at least a part of the above-mentioned problems, and is achieved by any of the following aspects.

[0014] One embodiment of the binder composition for a storage battery device according to the present invention comprises a polymer (A) and an emulsifier (B), wherein the emulsifier (B) is present in an amount of 30 to 30,000 ppm based on the total mass of the polymer (A).

[0015] When the total amount of the repeating units contained in the polymer (A) is 100% by mass, the polymer (A) contains:

[0016] 1 to 50% by mass of repeating units (a1) derived from an aromatic vinyl compound, and

[0017] The repeating unit (a2) derived from an unsaturated carboxylic acid ester is 20 to 75% by mass.

[0018] In one embodiment of the binder composition for an electrical storage device,

[0019] The polymer (A) may further contain 0.5 to 10% by mass of a repeating unit (a3) ​​derived from an unsaturated carboxylic acid.

[0020] In any one embodiment of the above-mentioned binder composition for electrical storage devices,

[0021] The polymer (A) may further contain 5 to 40% by mass of a repeating unit (a4) derived from an α,β-unsaturated nitrile compound.

[0022] In any one embodiment of the above-mentioned binder composition for electrical storage devices,

[0023] The polymer (A) may further contain 0.1 to 10% by mass of a repeating unit (a5) derived from a compound having a sulfonic acid group.

[0024] In any one embodiment of the above-mentioned binder composition for electrical storage devices,

[0025] The polymer (A) may further contain 0.1 to 10% by mass of a repeating unit (a6) derived from (meth)acrylamide.

[0026] In any one embodiment of the above-mentioned binder composition for electrical storage devices,

[0027] The polymer (A) may further contain 5 to 40% by mass of a repeating unit (a7) derived from vinyl pyrrolidone.

[0028] In any one embodiment of the above-mentioned binder composition for electrical storage devices,

[0029] The solubility of the polymer (A) in N-methyl-2-pyrrolidone at 25° C. and 1 atm may be 1 g or more per 100 g of N-methyl-2-pyrrolidone.

[0030] In any one embodiment of the above-mentioned binder composition for electrical storage devices,

[0031] The emulsifier (B) may be an anionic surfactant.

[0032] In any embodiment of the above-mentioned binder composition for electrical storage devices, a liquid medium (C) may be further contained.

[0033] The liquid medium (C) is at least one selected from aliphatic hydrocarbons, alicyclic hydrocarbons, aromatic hydrocarbons, ketones, esters, ethers, glycol ethers, lactams, lactones, and amides.

[0034] One embodiment of the slurry for electrical storage device electrodes according to the present invention contains the binder composition for electrical storage devices according to any of the above embodiments and an active material.

[0035] In one embodiment of the above-mentioned slurry for electrical storage device electrodes,

[0036] The active material may be a positive electrode active material.

[0037] One embodiment of an electrical storage device electrode according to the present invention includes a current collector and an active material layer formed by applying the electrical storage device electrode slurry of the embodiment described above to the surface of the current collector and drying the coating.

[0038] One embodiment of an electric storage device according to the present invention includes the electric storage device electrode of the above embodiment.

[0039] According to the binder composition for an electrical storage device according to the present invention, it is possible to produce an electrical storage device electrode having excellent surface condition, adhesion, and ion conductivity, and to provide an electrical storage device having excellent cycle life characteristics. DETAILED DESCRIPTION

[0040] The preferred embodiments of the present invention are described in detail below. However, the present invention is not limited to the embodiments described below, and should be understood to include various modifications that do not change the spirit of the present invention.

[0041] In this specification, "(meth)acrylic acid-" means "acrylic acid-" or "methacrylic acid-", "-(meth)acrylate" means "-acrylate" or "-methacrylate", and "(meth)acrylamide" means "acrylamide" or "methacrylamide".

[0042] In this specification, the numerical range described in the format of "X to Y" should be interpreted as including the numerical value X as the lower limit and the numerical value Y as the upper limit.

[0043] 1. Binder composition for electrical storage devices

[0044] An electrical storage device binder composition according to one embodiment of the present invention comprises a polymer (A) and an emulsifier (B), wherein the emulsifier (B) is present in an amount of 30 to 30,000 ppm relative to the total mass of the polymer (A). The components that may be included in the electrical storage device binder composition according to this embodiment are described in detail below.

[0045] 1.1. Polymer (A)

[0046] The binder composition for storage devices involved in this embodiment contains polymer (A). Polymer (A) can be in the form of a latex dispersed in a liquid medium (C) described later, or in the form of a state dissolved in the liquid medium (C), but is preferably in the form of a state dissolved in the liquid medium (C). If the polymer (A) is in the form of a state dissolved in the liquid medium (C), the stability of the composition (hereinafter also referred to as "slurry") prepared by mixing with the active material becomes good, and the coating property of the slurry on the collector becomes good, so it is preferred. Furthermore, if it is in a solution state, the adhesion strength between the active materials is improved and the ion conductivity is improved. Thus, the rise in internal resistance can be suppressed, and a storage device with excellent cycle life characteristics can be easily obtained.

[0047] The repeating units constituting the polymer (A), the physical properties of the polymer (A), and the production method are described below in this order.

[0048] 1.1.1. Repeating units constituting polymer (A)

[0049] When the total amount of repeating units contained in the polymer (A) is 100% by mass, the polymer (A) contains 1 to 50% by mass of repeating units (a1) derived from an aromatic vinyl compound (hereinafter also referred to as "repeating units (a1)") and 20 to 75% by mass of repeating units (a2) derived from an unsaturated carboxylic acid ester (hereinafter also referred to as "repeating units (a2)". In addition to the repeating units (a1) and the repeating units (a2), the polymer (A) may contain repeating units derived from other monomers copolymerizable with these.

[0050] 1.1.1.1. Repeating units (a1) derived from aromatic vinyl compounds

[0051] When the total of the repeating units contained in the polymer (A) is set to 100% by mass, the content of the repeating units (a1) from the aromatic vinyl compound is 1 to 50% by mass. The lower limit of the content of the repeating unit (a1) is preferably 2% by mass, more preferably 4% by mass. The upper limit of the content of the repeating unit (a1) is preferably 48% by mass, more preferably 45% by mass. By making the polymer (A) contain the repeating unit (a1) within the above range, good slurry properties are exhibited, and coating properties can be improved. In addition, the permeability of the electrolyte can be improved, and therefore good repeated charge and discharge characteristics are sometimes exhibited. In addition, good binding force is sometimes exhibited on the graphite used as an active material, and an electrical storage device electrode with excellent adhesion can be obtained.

[0052] The aromatic vinyl compound is not particularly limited, and examples thereof include styrene, α-methylstyrene, p-methylstyrene, vinyltoluene, chlorostyrene, and divinylbenzene. One or more kinds selected from these can be used. Among these, styrene is particularly preferred.

[0053] 1.1.1.2. Repeating units (a2) derived from unsaturated carboxylic acid esters

[0054] When the total amount of repeating units contained in the polymer (A) is 100% by mass, the content of the repeating units (a2) derived from the unsaturated carboxylic acid ester is 20 to 75% by mass. The lower limit of the content of the repeating units (a2) is preferably 22% by mass, more preferably 25% by mass. The upper limit of the content of the repeating units (a2) is preferably 68% by mass, more preferably 65% ​​by mass. By making the polymer (A) contain the repeating units (a2) within the above range, the affinity of the polymer (A) with the electrolyte becomes good, and the increase in internal resistance caused by the binder becoming a resistance component in the storage device can be suppressed.

[0055] Among the unsaturated carboxylates, aliphatic unsaturated carboxylates are particularly preferred. Among these, (meth)acrylates and itaconic acid diesters can be preferably used. As specific examples of (meth)acrylates, for example, methyl (meth)acrylate, ethyl (meth)acrylate, n-propyl (meth)acrylate, isopropyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, n-pentyl (meth)acrylate, isopentyl (meth)acrylate, hexyl (meth)acrylate, cyclohexyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, n-octyl (meth)acrylate, nonyl (meth)acrylate, decyl (meth)acrylate, ethylene glycol di(meth)acrylate, propylene ... Glycol esters, trimethylolpropane tri(meth)acrylate, pentaerythritol tetra(meth)acrylate, dipentaerythritol hexa(meth)acrylate, allyl(meth)acrylate, hydroxymethyl(meth)acrylate, 2-hydroxyethyl(meth)acrylate, 2-hydroxypropyl(meth)acrylate, 3-hydroxypropyl(meth)acrylate, 4-hydroxybutyl(meth)acrylate, 5-hydroxypentyl(meth)acrylate, 6-hydroxyhexyl(meth)acrylate, glycerol mono(meth)acrylate, and glycerol di(meth)acrylate can be used. Specific examples of itaconic acid diesters include dimethyl itaconate, diethyl itaconate, 1-ethyl-4-methyl itaconate, dipropyl itaconate, diisopropyl itaconate, and dibutyl itaconate. One or more selected from these can be used. Among these, at least one selected from methyl (meth)acrylate, ethyl (meth)acrylate, n-butyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, cyclohexyl (meth)acrylate, and hydroxyethyl (meth)acrylate is preferred, and at least one selected from methyl (meth)acrylate, n-butyl (meth)acrylate, and 2-ethylhexyl (meth)acrylate is more preferred.

[0056] 1.1.1.3. Other repeating units

[0057] In addition to the repeating units (a1) and (a2), the polymer (A) may contain repeating units derived from other monomers copolymerizable therewith. Examples of such repeating units include repeating units (a3) ​​derived from unsaturated carboxylic acids (hereinafter also referred to as "repeating units (a3)"), repeating units (a4) derived from α,β-unsaturated nitrile compounds (hereinafter also referred to as "repeating units (a4)"), repeating units (a5) derived from compounds having sulfonic acid groups (hereinafter also referred to as "repeating units (a5)"), repeating units (a6) derived from (meth)acrylamide (hereinafter also referred to as "repeating units (a6)"), repeating units (a7) derived from vinylpyrrolidone (hereinafter also referred to as "repeating units (a7)"), and repeating units derived from cationic monomers.

[0058] <Repeating unit (a3) ​​derived from unsaturated carboxylic acid>

[0059] Polymer (A) can contain repeating units (a3) ​​from unsaturated carboxylic acid. When the total of the repeating units included in polymer (A) is set to 100 mass %, the containing ratio of repeating units (a3) ​​is preferably 0.5 to 10 mass %. The lower limit of the containing ratio of repeating units (a3) ​​is more preferably 0.7 mass %, particularly preferably 1 mass %. The upper limit of the containing ratio of repeating units (a3) ​​is more preferably 9 mass %, particularly preferably 8 mass %. Sometimes by making polymer (A) contain repeating units (a3) ​​within the above range, it is possible to improve the binding property of collector and active material layer, and the adhesion strength of electrode improves.

[0060] The unsaturated carboxylic acid is not particularly limited, and examples thereof include monocarboxylic acids such as acrylic acid, methacrylic acid, and crotonic acid; dicarboxylic acids (including anhydrides) such as maleic acid, fumaric acid, and itaconic acid; and monoesters thereof. At least one selected from these can be used. Of these, at least one selected from acrylic acid, methacrylic acid, itaconic acid, and itaconic acid monoesters is preferably used. Specific examples of itaconic acid monoesters include monobutyl itaconate, monoethyl itaconate, monopropyl itaconate, monoisopropyl itaconate, and monobutyl itaconate.

[0061] <Repeating unit (a4) derived from an α,β-unsaturated nitrile compound>

[0062] Polymer (A) may contain repeating units (a4) from α, β-unsaturated nitrile compounds. When the total of the repeating units contained in the polymer (A) is set to 100% by mass, the content of the repeating units (a4) is preferably 5 to 40% by mass. The lower limit of the content of the repeating units (a4) is more preferably 6% by mass, particularly preferably 7% by mass. The upper limit of the content of the repeating units (a4) is more preferably 38% by mass, particularly preferably 35% by mass. By making the polymer (A) contain repeating units (a4) within the above range, the affinity of the polymer (A) and the electrolyte becomes good, and sometimes it is possible to suppress the rise of the internal resistance occupied by the binder as a resistance component in the storage device.

[0063] The α,β-unsaturated nitrile compound is not particularly limited, and examples thereof include acrylonitrile, methacrylonitrile, α-chloroacrylonitrile, α-ethylacrylonitrile, vinylidene cyanide, isopropylidene malononitrile, fumaric acid nitrile, and tetracyanoethylene. At least one selected from these can be used. Among these, at least one selected from acrylonitrile, methacrylonitrile, isopropylidene malononitrile, fumaric acid nitrile, and tetracyanoethylene is preferred, and at least one selected from acrylonitrile, isopropylidene malononitrile, fumaric acid nitrile, and tetracyanoethylene is more preferred.

[0064] <Repeating unit (a5) derived from a compound having a sulfonic acid group>

[0065] The polymer (A) may contain repeating units (a5) derived from a compound having a sulfonic acid group. The compound having a sulfonic acid group is not particularly limited, and examples thereof include vinylsulfonic acid, styrenesulfonic acid, allylsulfonic acid, sulfoethyl (meth)acrylate, sulfopropyl (meth)acrylate, sulfobutyl (meth)acrylate, 2-acrylamide-2-methylpropanesulfonic acid, tert-butyl acrylamidesulfonate, 2-hydroxy-3-acrylamidepropanesulfonic acid, 3-allyloxy-2-hydroxypropanesulfonic acid, and alkali salts thereof. At least one selected from these compounds may be used.

[0066] When the total amount of repeating units contained in the polymer (A) is 100% by mass, the content of the repeating units (a5) derived from the compound having a sulfonic acid group is preferably 0.1 to 10% by mass. The lower limit of the content of the repeating units (a5) is more preferably 0.5% by mass, particularly preferably 1% by mass. The upper limit of the content of the repeating units (a5) is more preferably 8% by mass, particularly preferably 6% by mass. By making the polymer (A) contain the repeating units (a5) within the above range, the dispersibility of the active material and the filler becomes good, and a homogeneous active material layer and a protective film can be produced. Therefore, the structural defects of the electrode plate disappear, and good charge and discharge characteristics are sometimes exhibited.

[0067] <Repeating unit (a6) derived from (meth)acrylamide>

[0068] Polymer (A) may contain repeating units (a6) from (meth) acrylamide. When the total of the repeating units contained in polymer (A) is set to 100% by mass, the content ratio of repeating units (a6) is preferably 0 to 10% by mass. The lower limit of the content ratio of repeating units (a6) is more preferably 0.5% by mass, particularly preferably 1% by mass. The upper limit of the content ratio of repeating units (a6) is more preferably 8% by mass, particularly preferably 6% by mass. By making polymer (A) contain repeating units (a6) within the above range, the dispersibility of the active material in the slurry sometimes becomes good. In addition, the softness of the active material layer obtained sometimes becomes appropriate, and the adhesion of the current collector to the active material layer is improved. Moreover, the binding ability of active materials such as NMC and NCA to each other can be improved, so that sometimes an active material layer with better softness and adhesion to the current collector can be obtained.

[0069] The (meth)acrylamide is not particularly limited, and examples thereof include acrylamide, methacrylamide, N-isopropylacrylamide, N,N-dimethylacrylamide, N,N-dimethylmethacrylamide, N,N-diethylacrylamide, N,N-diethylmethacrylamide, N,N-dimethylaminopropylacrylamide, N,N-dimethylaminopropylmethacrylamide, N-methylolacrylamide, N-methylolmethacrylamide, diacetoneacrylamide, maleamide, and t-butyl acrylamidesulfonate. At least one selected from these can be used.

[0070] <Repeating unit (a7) derived from vinylpyrrolidone>

[0071] Polymer (A) may contain repeating units (a7) from vinyl pyrrolidone. When the total of the repeating units contained in polymer (A) is set to 100% by mass, the content ratio of repeating units (a7) is preferably 5 to 40% by mass. The lower limit of the content ratio of repeating units (a7) is more preferably 6% by mass, particularly preferably 7% by mass. The upper limit of the content ratio of repeating units (a7) is more preferably 38% by mass, particularly preferably 35% by mass. By making polymer (A) contain repeating units (a7) within the above range, the affinity of the polymer (A) and the electrolyte becomes good, and sometimes it is possible to suppress the rise of the internal resistance caused by the binder becoming a resistance component in the storage device.

[0072] <Repeating unit derived from a cationic monomer>

[0073] Polymer (A) may contain repeating units from cationic monomers. There are no particular limitations on the cationic monomers, but at least one monomer selected from secondary amines (salts), tertiary amines (salts), and quaternary ammonium salts is preferred. Specific examples of cationic monomers include 2-(dimethylamino)ethyl (meth)acrylate, dimethylaminoethyl (meth)acrylate methyl chloride quaternary salt, 2-(diethylamino)ethyl (meth)acrylate, 3-(dimethylamino)propyl (meth)acrylate, 3-(diethylamino)propyl (meth)acrylate, 4-(dimethylamino)phenyl (meth)acrylate, 2-[(3,5-dimethylpyrazolyl)carbonylamino]ethyl (meth)acrylate, 2-(0-[1'-methylpropylideneamino]carboxylamino)ethyl (meth)acrylate, 2-(1-aziridinyl)ethyl (meth)acrylate, methacryloyloxyethyl trimethylammonium chloride, tris(2-propylene glycol)isocyanurate, and the like. The following examples include 1,2-di(2-pyridyl)ethylene, 4'-hydrazino-2-stilbeneazole dihydrochloride hydrate, 4-(4-dimethylaminostyryl)quinoline, 1-vinylimidazole, diallylamine, diallylamine hydrochloride, triallylamine, diallyldimethylammonium chloride, dichloroallylamine, N-allylbenzylamine, N-allylaniline, 2,4-diamino-6-diallylamino-1,3,5-triazine, N-trans-cinnamyl-N-methyl-(1-naphthylmethyl)amine hydrochloride, and trans-N-(6,6-dimethyl-2-heptene-4-ynyl)-N-methyl-1-naphthylmethylamine hydrochloride. At least one selected from these may be used.

[0074] 1.1.2. Physical properties of polymer (A)

[0075] 1.1.2.1. Weight average molecular weight (Mw) of THF-soluble component

[0076] The weight average molecular weight (Mw) of the THF (tetrahydrofuran) soluble component of the polymer (A) measured by gel permeation chromatography (GPC) in terms of polystyrene is preferably 3 to 70% of the total area of ​​the peak obtained, more preferably 4 to 68%, and particularly preferably 5 to 65%. If the weight average molecular weight (Mw) of the polymer (A) is 1,000,000 or more and the ratio is within the above range, the stability of the slurry prepared by mixing with the active material becomes good, and the coating property of the slurry on the collector becomes good. In addition, the use of polymer (A) can improve the adhesion between fillers such as active materials and conductive additives, and a lithium ion secondary battery with excellent charge and discharge characteristics can be easily obtained. In addition, when making lithium ion secondary batteries, the resistance of the electrode plate to external forces such as pressing and bending is improved. It should be noted that the weight average molecular weight of the THF soluble component can be measured using the method described in the examples of this specification.

[0077] 1.1.2.2. Solubility in N-methyl-2-pyrrolidone

[0078] The solubility of polymer (A) in N-methyl-2-pyrrolidone (also referred to as "NMP" in this specification) at 25°C and 1 atmosphere is preferably 1 g or more relative to 100 g of NMP. The solubility in NMP of 1 g or more relative to NMP means that polymer (A) is soluble in organic solvents. If polymer (A) is soluble in organic solvents, the surface of the active material can be easily coated with the polymer (A) due to its excellent softness and adhesion, thereby effectively suppressing the shedding caused by the expansion and contraction of the active material during charge and discharge, and easily obtaining a storage device exhibiting good charge and discharge durability characteristics. In addition, the stability of the slurry becomes good, and the coating property of the slurry on the collector also becomes good, so it is preferred.

[0079] 1.1.3. Method for producing polymer (A)

[0080] <Polymerization process>

[0081] The synthesis of the polymer (A) is not particularly limited, and for example, an emulsion polymerization method in the presence of a known emulsifier, chain transfer agent, polymerization initiator, etc. can be employed.

[0082] Examples of the emulsifier include anionic surfactants such as sulfate esters of higher alcohols, alkylbenzenesulfonates, alkylnaphthalenesulfonates, dialkylsulfosuccinates, alkyldiphenylether disulfonates, aliphatic sulfonates, aliphatic carboxylates, dehydroabietic acid salts, naphthalenesulfonic acid-formaldehyde condensates, and sulfate esters of nonionic surfactants; nonionic surfactants such as alkyl esters of polyethylene glycol, alkylphenyl ethers of polyethylene glycol, and alkyl ethers of polyethylene glycol; fluorinated surfactants such as perfluorobutylsulfonates, perfluoroalkyl-containing phosphates, perfluoroalkyl-containing carboxylates, and perfluoroalkyl ethylene oxide adducts, and at least one selected from these can be used.

[0083] As the chain transfer agent and the polymerization initiator, for example, compounds described in Japanese Patent No. 5999399 can be used.

[0084] The emulsion polymerization method for synthesizing the polymer (A) may be carried out by a single-stage polymerization or a multi-stage polymerization of two or more stages.

[0085] When polymer (A) is synthesized by one-stage polymerization, the above-mentioned monomer mixture can be subjected to emulsion polymerization in the presence of a suitable emulsifier, chain transfer agent, polymerization initiator, etc., at a temperature preferably between 0 and 80° C., and for a polymerization time preferably between 4 and 36 hours.

[0086] When the polymer (A) is synthesized by two-stage polymerization, the polymerization in each stage is preferably set as follows.

[0087] The ratio of the monomers used in the first-stage polymerization relative to the total weight of the monomers (the sum of the weight of the monomers used in the first-stage polymerization and the weight of the monomers used in the second-stage polymerization) is preferably 20 to 99% by weight, and more preferably 25 to 99% by weight. Carrying out the first-stage polymerization at such a ratio of monomers is preferred because it allows the production of polymer (A) particles having excellent dispersion stability and being less likely to form aggregates, and also suppresses the increase in viscosity over time of the binder composition for a storage battery device after solidification.

[0088] The types and proportions of the monomers used in the second stage polymerization may be the same as or different from those used in the first stage polymerization.

[0089] From the viewpoint of the dispersibility of the particles of the obtained polymer (A), the polymerization conditions in each stage are preferably as follows.

[0090] First stage polymerization: preferably a temperature of 0 to 80° C., preferably a polymerization time of 2 to 36 hours, and preferably a polymerization conversion rate of 50% by mass or more, more preferably 60% by mass or more.

[0091] Second stage polymerization: The temperature is preferably 0 to 80° C., and the polymerization time is preferably 2 to 18 hours.

[0092] When the polymer (A) is synthesized by three-stage polymerization, the polymerization in each stage is preferably set as follows.

[0093] The ratio of the monomers used in the first-stage polymerization relative to the total weight of the monomers (the sum of the weight of the monomers used in the first-stage polymerization, the weight of the monomers used in the second-stage polymerization, and the weight of the monomers used in the third-stage polymerization) is preferably 20 to 90% by weight, and more preferably 25 to 80% by weight. By carrying out the first-stage polymerization with such a ratio of monomers, particles of the polymer (A) having excellent dispersion stability and being less likely to form aggregates can be obtained, and the increase in viscosity over time of the binder composition for a storage battery device after solidification is also suppressed, which is preferred.

[0094] The types and proportions of the monomers used in the second stage polymerization may be the same as or different from those used in the first stage polymerization.

[0095] The types and proportions of monomers used in the third stage polymerization may be the same as or different from those used in the first stage polymerization and the second stage polymerization.

[0096] From the viewpoint of the dispersibility of the particles of the obtained polymer (A), the polymerization conditions in each stage are preferably as follows.

[0097] First stage polymerization: preferably a temperature of 0 to 80° C., preferably a polymerization time of 2 to 36 hours, and preferably a polymerization conversion rate of 50% by mass or more, more preferably 60% by mass or more.

[0098] Second stage polymerization: The temperature is preferably 0 to 80° C., and the polymerization time is preferably 2 to 18 hours.

[0099] The third stage polymerization is preferably carried out at a temperature of 0 to 80° C. and for a polymerization time of 2 to 9 hours.

[0100] By setting the total solids concentration in the emulsion polymerization to 50% by mass or less, the polymerization reaction can be carried out with good dispersion stability of the obtained polymer (A) particles. The total solids concentration is preferably 45% by mass or less, more preferably 40% by mass or less.

[0101] Whether the synthesis of polymer (A) is carried out by single-stage polymerization or multi-stage polymerization, it is preferred to add a neutralizing agent to the polymerization mixture after the completion of the emulsion polymerization for neutralization. The neutralizing agent used herein is not particularly limited, and examples thereof include metal hydroxides such as sodium hydroxide and potassium hydroxide, and ammonia.

[0102] <Solidification process>

[0103] Next, a coagulant is added to the emulsion polymer solution obtained in the above-mentioned polymerization step to coagulate the polymer, thereby obtaining hydrous pellets (a coagulant containing the polymer, the coagulant, and water).

[0104] As the coagulant, monovalent to trivalent metal salts are preferably used, examples of which include magnesium sulfate, sodium chloride, and calcium chloride. Of these, sodium chloride and calcium chloride are preferred. The amount of the coagulant used is preferably 1 to 20 parts by mass, more preferably 2 to 15 parts by mass, per 100 parts by mass of the polymer in the emulsion polymerization solution.

[0105] The solidification temperature is not particularly limited, but is preferably 40°C to 90°C, more preferably 45°C to 80°C.

[0106] <Cleaning process>

[0107] Next, the water-containing pellets obtained in the above-mentioned coagulation step are washed. By washing the water-containing pellets, the amount of residual components other than the polymer (coagulant, etc.) can be reduced.

[0108] The washing method is not particularly limited, but examples thereof include a method in which water is used as the washing liquid and the water added together with the hydrous pellets is mixed for washing. The temperature during washing is not particularly limited, but is preferably 5°C to 70°C, more preferably 10°C to 60°C. The mixing time is not particularly limited, but is preferably 1 minute to 60 minutes, more preferably 2 minutes to 45 minutes.

[0109] Furthermore, the amount of water added to the hydrous pellets during water washing is not particularly limited. However, from the viewpoint of effectively reducing the content (residual amount) of the coagulant in the finally obtained electrical storage device binder composition, the amount is preferably 150 to 10,000 parts by mass, and more preferably 150 to 5,000 parts by mass, relative to 100 parts by mass of the polymer contained in the hydrous pellets.

[0110] As the number of water washings, there is no particular limitation, and it can be 1 time, but from the viewpoint of reducing the content (residual amount) of the coagulant in the final storage device binder composition, it is preferably 2 to 10 times, more preferably 3 to 8 times. It should be noted that from the viewpoint of reducing the content (residual amount) of the coagulant in the final storage device binder composition, the more water washings the better, but even if the above range is exceeded for cleaning, the removal effect of the coagulant is also small. On the other hand, increasing the number of steps, the impact of the decline in manufacturing efficiency becomes larger. In addition, in order to further reduce the content (residual amount) of the coagulant, it is necessary to temporarily dissolve it in an organic solvent such as toluene and then put it into a completely independent other process such as methanol to solidify it. Therefore, it is preferably carried out by a coagulation water washing method with good industrial manufacturing efficiency, and the number of water washings is preferably within the above range. In addition, after washing in the cleaning process, acid can be further used as a cleaning solution for acid cleaning.

[0111] <Drying process>

[0112] Next, the hydrous pellets that have undergone the above-described washing step are dried to obtain a coagulated and dried product containing the polymer and the coagulant. The drying method that can be used in the drying step is not particularly limited, and for example, drying can be performed using a screw extruder, a kneading dryer, an expansion dryer, a hot air dryer, a reduced pressure dryer, or other dryers. Furthermore, a combination of these drying methods may be used. Furthermore, before drying in the drying step, the hydrous pellets may be filtered using a rotary sieve, a vibrating sieve, or a centrifugal dehydrator, as needed.

[0113] The drying temperature in the drying step is not particularly limited and varies depending on the dryer used for drying. For example, when a hot air dryer is used, the drying temperature is preferably 60°C to 200°C, more preferably 70°C to 180°C.

[0114] 1.2. Emulsifier (B)

[0115] The binder composition for storage devices according to the present embodiment contains an emulsifier (B), and the emulsifier (B) is 30 to 30,000 ppm relative to the total mass of the polymer (A). The lower limit of the content ratio of the emulsifier (B) is preferably 50 ppm, more preferably 100 ppm, relative to the total mass of the above-mentioned polymer (A). The upper limit of the content ratio of the emulsifier (B) is preferably 25,000 ppm, more preferably 20,000 ppm, relative to the total mass of the above-mentioned polymer (A). By containing the emulsifier (B) in the above-mentioned proportion, the fusion of the binders in the slurry coating film can be suppressed, the increase in internal resistance can be suppressed, and good repeated charge and discharge characteristics can be exhibited. In addition, the generation of dents on the surface of the slurry coating film caused by broken bubbles originating from the emulsifier can be suppressed.

[0116] As mentioned above, an emulsifier is used during the polymerization of polymer (A), but the amount of residual emulsifier varies depending on the conditions of the subsequent coagulation process, cleaning process, etc. Therefore, it is generally impossible to properly manage the residual emulsifier. It was found that the binder composition for storage devices of the present invention exhibits good battery characteristics by properly managing the amount of emulsifier in the manufacturing process. That is, if the amount of emulsifier is below the above upper limit, it is possible to effectively suppress the formation of dents on the surface of the slurry coating caused by broken bubbles originating from the emulsifier. In addition, if the amount of emulsifier is above the above lower limit, it is possible to suppress the fusion of the binders in the slurry coating, suppress the increase in internal resistance, and thus exhibit good repeated charge and discharge characteristics. In particular, if the electrode layer cannot maintain an electronic conductive path, the lithium ion conductivity decreases and the resistance increases, so it is important to suppress the obstruction of the conductive path caused by the fusion of the binders.

[0117] Examples of the emulsifier (B) include the emulsifiers exemplified in the polymerization step above. Among these, anionic surfactants are preferred, and alkylbenzenesulfonates, alkylnaphthalenesulfonates, dialkylsulfosuccinates, alkyldiphenyletherdisulfonates, aliphatic sulfonates, aliphatic carboxylates, and dehydroabietic acid salts are more preferred.

[0118] 1.3. Liquid medium (C)

[0119] The binder composition for an electrical storage device according to this embodiment contains a liquid medium (C). The liquid medium (C) is not particularly limited and may include aliphatic hydrocarbons such as hexane, heptane, octane, decane, and dodecane; alicyclic hydrocarbons such as cyclohexane, cycloheptane, cyclooctane, and cyclodecane; aromatic hydrocarbons such as toluene, xylene, mesitylene, naphthalene, and tetralin; ketones such as methyl hexanone and dipropyl ketone; esters such as butyl acetate, butyl butyrate, and methyl butyrate; ethers such as dibutyl ether, tetrahydrofuran, and anisole; lactams such as N-methyl-2-pyrrolidone and 2-pyrrolidone; amides such as N-methylacetamide, dimethylacetamide, N-methylformamide, and dimethylformamide; lactams such as β-lactam, γ-lactam, and σ-lactam; glycol ethers such as (mono-, di-, tri-, and poly)ethylene glycol monomethyl ether, (mono-, di-, tri-, and poly)ethylene glycol dimethyl ether, and ethylene glycol phenyl ether; and aqueous media containing water. These solvents can be used alone or in combination of two or more.

[0120] The content ratio of the liquid medium (C) in the binder composition for storage devices according to the present embodiment is preferably 100 to 10,000 parts by mass, more preferably 500 to 2,000 parts by mass, relative to 100 parts by mass of the polymer (A). If the content ratio of the liquid medium (C) is above the above lower limit, the miscibility of the polymer (A) and the active material becomes good when the slurry is prepared. On the other hand, if the content ratio of the liquid medium (C) is below the above upper limit, the coating property of the slurry becomes good when the active material layer is manufactured, and it is not easy to generate a concentration gradient of the polymer (A) and the active material in the drying process after coating. In addition, when manufacturing the electrode layer, the coating property of the slurry containing the active material, the conductive auxiliary agent and the binder composition for storage devices becomes good, and it is not easy to generate a concentration gradient of the polymer (A) in the drying process after coating.

[0121] 1.4. Other additives

[0122] The binder composition for electrical storage devices according to this embodiment may contain additives other than the above-mentioned components as needed. Examples of such additives include polymers other than the polymer (A), antioxidants, and thickeners.

[0123] <Polymers other than polymer (A)>

[0124] The storage device binder composition involved in the present embodiment may contain polymers other than polymer (A). As such polymers, there is no particular limitation, and examples include acrylic polymers, PVDF (polyvinylidene fluoride) and other fluorine-based polymers containing unsaturated carboxylic acid esters or their derivatives as constituent units. These polymers may be used alone or in combination of two or more. By containing these polymers, flexibility and adhesion are sometimes further improved.

[0125] <Antioxidants>

[0126] The binder composition for a storage device according to this embodiment may contain an antioxidant. The inclusion of an antioxidant may further improve the low-temperature cycle characteristics and low-temperature output characteristics of the resulting storage device. In addition, the oxidation resistance of the polymer component may be further improved.

[0127] Examples of the antioxidant include compounds such as phenolic antioxidants, amine antioxidants, quinone antioxidants, organophosphorus antioxidants, sulfur antioxidants, and phenothiazine antioxidants. Among these, phenolic antioxidants and amine antioxidants are preferred.

[0128] Thickener

[0129] The electrical storage device binder composition according to this embodiment may contain a thickener. By containing a thickener, the coating properties of the slurry and the charge and discharge characteristics of the resulting electrical storage device may be further improved.

[0130] Examples of thickeners include cellulose polymers such as carboxymethyl cellulose, methyl cellulose, ethyl cellulose, and hydroxypropyl cellulose; poly(meth)acrylic acid; ammonium salts or alkali metal salts of the above-mentioned cellulose compounds or poly(meth)acrylic acid; modified polyvinyl alcohol, polyethylene oxide; polyvinyl pyrrolidone, polycarboxylic acids, oxidized starch, starch phosphate, casein, various modified starches, chitin, and chitosan derivatives. Among these, cellulose polymers are preferred.

[0131] Examples of commercially available products of these thickeners include alkali metal salts of carboxymethylcellulose such as CMC1120, CMC1150, CMC2200, CMC2280, and CMC2450 (all manufactured by Daicel Corporation).

[0132] When the electrical storage device binder composition according to this embodiment contains a thickener, the content of the thickener is preferably 5% by mass or less, more preferably 0.1 to 3% by mass, relative to 100% by mass of the total solid content of the electrical storage device binder composition.

[0133] 2. Slurry for electrodes of power storage devices

[0134] The slurry for an electrical storage device electrode according to one embodiment of the present invention contains the aforementioned electrical storage device binder composition and an active material. The slurry for an electrical storage device electrode according to this embodiment can be used as a material for producing an electrical storage device electrode (active material layer) that improves the binding ability between active materials, the adhesion ability between active materials and current collectors, and the resistance to powder shedding. Specifically, the active material layer can be produced on the surface of the current collector by applying the slurry for an electrical storage device electrode according to this embodiment to the surface of the current collector and then drying it.

[0135] Generally speaking, positive electrode slurries often contain PVDF to suppress increases in internal resistance. On the other hand, the electrical storage device electrode slurry according to this embodiment can suppress increases in internal resistance even when containing only the aforementioned polymer (A) as a polymer component. Of course, the electrical storage device electrode slurry according to this embodiment may contain polymers other than polymer (A) and thickeners to further suppress increases in internal resistance. The following describes the components that may be included in the electrical storage device electrode slurry according to this embodiment.

[0136] 2.1. Binder composition for electrical storage devices

[0137] The composition, physical properties, and production method of the binder composition for a storage battery device are as described above, and their description is omitted here.

[0138] The content ratio of the polymer component in the slurry for storage device electrodes according to this embodiment is preferably 0.5 to 10 parts by mass, more preferably 1 to 8 parts by mass, further preferably 1 to 7 parts by mass, and particularly preferably 1.5 to 6 parts by mass relative to 100 parts by mass of the active material. If the content ratio of the polymer component is within the above range, the dispersibility of the active material in the slurry becomes good and the coating property of the slurry also becomes excellent. Here, the polymer component includes polymer (A), polymers other than polymer (A) added as needed, and thickeners.

[0139] Active substances

[0140] Examples of the active material used in the slurry for storage device electrodes according to this embodiment include positive electrode active materials and negative electrode active materials. Specific examples thereof include carbon materials, silicon materials, oxides containing lithium atoms, sulfur compounds, lead compounds, tin compounds, arsenic compounds, antimony compounds, aluminum compounds, conductive polymers such as polyacene, and A X B Y O Z(wherein A is an alkali metal or a transition metal, B is at least one selected from transition metals such as cobalt, nickel, aluminum, tin, and manganese, O represents an oxygen atom, and X, Y, and Z are numbers in the range of 1.10>X>0.05, 4.00>Y>0.85, and 5.00>Z>1.5, respectively) composite metal oxides, other metal oxides, etc. Specific examples thereof include compounds described in Japanese Patent No. 5999399 and the like.

[0141] The slurry for electrical storage device electrodes according to the present embodiment can be used when producing either a positive electrode or a negative electrode, and is particularly preferably used for a positive electrode.

[0142] When preparing a positive electrode, an oxide containing lithium atoms is preferably used among the active materials exemplified above. Examples of the oxide containing lithium atoms include one or more selected from the group consisting of lithium manganate, lithium nickelate, lithium cobaltate, and lithium manganese nickel cobaltate represented by the following general formula (1).

[0143] Li 1-x M x (AO4)·····(1)

[0144] (In formula (1), M is an ion of at least one metal selected from the group consisting of Mg, Ti, V, Nb, Ta, Cr, Mn, Fe, Co, Ni, Cu, Zn, Al, Ga, Ge, and Sn; A is at least one metal selected from the group consisting of Si, S, P, and V; and x is a number satisfying the relationship 0<x<1.)

[0145] The value of x in the general formula (1) is selected based on the valences of M and A so that the valence of the general formula (1) as a whole becomes 0.

[0146] Examples of the olivine-type lithium-containing phosphate compound include LiFePO4, LiCoPO4, LiMnPO4, Li 0.9 0Ti 0.05 Nb 0.05 Fe 0.30 Co 0.30 Mn 0.30 PO 4 , etc. Among these, LiFePO 4 (lithium iron phosphate) is particularly preferred because the iron compound serving as the raw material is easily available and inexpensive.

[0147] The average particle size of the olivine-type lithium-containing phosphate compound is preferably in the range of 1 to 30 μm, more preferably in the range of 1 to 25 μm, and particularly preferably in the range of 1 to 20 μm.

[0148] In addition, the active material layer may contain the following active materials. For example, conductive polymers such as polyacene can be mentioned; A X B Y OZ (wherein A is an alkali metal or a transition metal, B is at least one selected from transition metals such as cobalt, nickel, aluminum, tin, and manganese, O represents an oxygen atom, and X, Y, and Z are numbers in the range of 1.10>X>0.05, 4.00>Y>0.85, and 5.00>Z>1.5, respectively.) Composite metal oxides, other metal oxides, etc.

[0149] Examples of the composite metal oxide include lithium cobalt oxide, lithium nickel oxide, lithium manganese oxide, and ternary nickel-cobalt-manganese oxide.

[0150] The electrical storage device electrode produced using the electrical storage device electrode slurry according to this embodiment exhibits excellent electrical properties even when an oxide containing lithium atoms is used as the positive electrode active material. This is believed to be because the polymer (A) can firmly bind the oxide containing lithium atoms and maintain the firmly bound state of the oxide containing lithium atoms even during charge and discharge.

[0151] On the other hand, when making the negative electrode, the active material exemplified above preferably contains a silicon material and / or a carbon material, and more preferably a mixture of a silicon material and a carbon material. Since the amount of lithium absorbed per unit weight of the silicon material is greater than that of other active materials, the storage capacity of the resulting storage device can be increased, and as a result, the output and energy density of the storage device can be increased. On the other hand, since the volume change of the carbon material accompanying charge and discharge is smaller than that of the silicon material, by using a mixture of a silicon material and a carbon material as the negative electrode active material, the influence of the volume change of the silicon material can be alleviated, and the adhesion between the active material layer and the collector can be further improved.

[0152] When silicon (Si) is used as the active material, it has a high capacity, but it also undergoes significant volume changes when absorbing lithium ions. Consequently, repeated expansion and contraction of silicon material can cause it to pulverize, leading to separation from the current collector, separation of the active material from each other, and the easy breakdown of the conductive network within the active material layer. This property can significantly degrade the charge and discharge durability of the storage device over a short period of time.

[0153] In this regard, the electrical storage device electrode produced using the electrical storage device electrode slurry according to this embodiment exhibits excellent electrical properties without causing the aforementioned problems even when using silicon materials. This is believed to be because the polymer (A) can firmly bond to the silicon material and, even when the silicon material expands in volume due to lithium absorption, the polymer (A) can expand and contract, maintaining a firm bond to the silicon material.

[0154] The content of the silicon material in 100% by mass of the active material is preferably 1% by mass or greater, more preferably 2 to 50% by mass, further preferably 3 to 45% by mass, and particularly preferably 10 to 40% by mass. When the content of the silicon material in 100% by mass of the active material is within this range, an electrical storage device having an excellent balance between improved output and energy density of the electrical storage device and charge and discharge durability characteristics can be obtained.

[0155] The active material is preferably in the form of particles and has an average particle size of preferably 0.1 to 100 μm, more preferably 1 to 20 μm.

[0156] 2.3. Other ingredients

[0157] In addition to the above-mentioned components, the slurry for storage device electrodes according to this embodiment may also contain, as needed, polymers other than polymer (A), thickeners, liquid media, conductive additives, pH adjusters, corrosion inhibitors, antioxidants, cellulose fibers, and other components. Polymers other than polymer (A) and thickeners can be appropriately selected from the compounds listed in the above section "1.4. Other Additives" and used for the same purpose and in the same proportions.

[0158] Liquid medium

[0159] In addition to the components introduced from the electrical storage device binder composition, a liquid medium may be further added to the electrical storage device electrode slurry according to this embodiment. The added liquid medium may be the same as or different from the liquid medium (C) contained in the electrical storage device binder composition. Preferably, the added liquid medium is selected from the liquid media exemplified in the above section "1.3. Liquid Medium (C)".

[0160] The content ratio of the liquid medium (including components introduced from the binder composition for a storage device) in the slurry for a storage device electrode according to this embodiment is preferably such that the solid content concentration in the slurry (referring to the ratio of the total mass of the components in the slurry other than the liquid medium to the total mass of the slurry; the same shall apply hereinafter) is 30 to 70% by mass, and more preferably 40 to 60% by mass.

[0161] <Conductive additives>

[0162] A conductive auxiliary agent may be further added to the slurry for electrical storage device electrodes according to this embodiment in order to impart conductivity and buffer the volume change of the active material caused by the entry and exit of lithium ions.

[0163] Specific examples of conductive additives include activated carbon, acetylene black, Ketjen black, furnace black, graphite, carbon fibers, fullerenes, carbon nanotubes, and the like. Of these, acetylene black, Ketjen black, and carbon nanotubes are preferably used. The content of the conductive additive relative to 100% by mass of the active material is preferably 20% by mass or less, more preferably 1 to 15% by mass, and particularly preferably 2 to 10% by mass.

[0164] pH adjuster

[0165] In order to suppress corrosion of the current collector depending on the type of active material, a pH adjuster may be further added to the slurry for electrical storage device electrodes according to this embodiment.

[0166] Examples of pH adjusters include hydrochloric acid, phosphoric acid, sulfuric acid, acetic acid, formic acid, ammonium phosphate, ammonium sulfate, ammonium acetate, ammonium formate, ammonium chloride, sodium hydroxide, and potassium hydroxide. Among these, sulfuric acid, ammonium sulfate, sodium hydroxide, and potassium hydroxide are preferred. Alternatively, a neutralizing agent may be selected from the neutralizing agents described in the method for producing the polymer (A).

[0167] <Anti-corrosion agent>

[0168] In order to suppress corrosion of the current collector depending on the type of active material, an anti-corrosion agent may be further added to the slurry for electrical storage device electrodes according to this embodiment.

[0169] Examples of corrosion inhibitors include ammonium metavanadate, sodium metavanadate, potassium metavanadate, ammonium metatungstate, sodium metatungstate, potassium metatungstate, ammonium paratungstate, sodium paratungstate, potassium paratungstate, ammonium molybdate, sodium molybdate, and potassium molybdate. Among these, ammonium paratungstate, ammonium metavanadate, sodium metavanadate, potassium metavanadate, and ammonium molybdate are preferred.

[0170] Cellulose fiber

[0171] Cellulose fibers may be further added to the slurry for storage device electrodes according to the present embodiment. As the cellulose fibers, known cellulose fibers may be used. By adding cellulose fibers, the adhesion of the active material to the current collector may sometimes be improved. It is believed that by utilizing line bonding or line contact through the fibrous cellulose fibers to bond adjacent active materials to each other in a fibrous manner, the active material can be prevented from falling off and the adhesion to the current collector can be improved.

[0172] 2.4. Preparation of Slurry for Electrical Storage Device Electrodes

[0173] The slurry for the storage device electrodes of this embodiment can be manufactured by any method as long as it contains the above-mentioned storage device binder composition and active material. From the perspective of more efficiently and cheaply manufacturing a slurry with better dispersibility and stability, it is preferably manufactured by adding the active material and any additional components used as needed to the storage device binder composition and mixing them. As a specific manufacturing method, for example, the method described in Japanese Patent No. 5999399 can be cited.

[0174] 3.Electrodes for energy storage devices

[0175] An electrical storage device electrode according to one embodiment of the present invention comprises a current collector and an active material layer formed by applying the above-mentioned electrical storage device electrode slurry on the surface of the above-mentioned current collector and drying it. The above-mentioned electrical storage device electrode can be manufactured by applying the above-mentioned electrical storage device electrode slurry on the surface of a current collector such as a metal foil to form a coating film, and then drying the coating film to form an active material layer. The electrical storage device electrode thus manufactured is formed by bonding an active material layer containing the above-mentioned polymer (A), an active material, and any components added as needed to the surface of the current collector. Therefore, the surface of the active material layer has few defects, is in a good state, and has excellent adhesion and ion conductivity.

[0176] The current collector is not particularly limited as long as it is made of a conductive material, and examples thereof include current collectors described in Japanese Patent No. 5999399 and the like.

[0177] In the electrical storage device electrode according to this embodiment, when a silicon material is used as the active material, the silicon content in 100% by mass of the active material layer is preferably 1 to 30% by mass, more preferably 2 to 20% by mass, and particularly preferably 3 to 10% by mass. If the silicon content in the active material layer is within this range, not only will the storage capacity of the electrical storage device produced using the active material layer be improved, but an active material layer with a uniform distribution of silicon will also be obtained. The silicon content in the active material layer can be measured, for example, by the method described in Japanese Patent No. 5999399.

[0178] 4.Electrical storage equipment

[0179] An electrical storage device according to one embodiment of the present invention can be manufactured using conventional methods by including the above-described electrical storage device electrodes, further comprising an electrolyte, and using components such as separators. Specific manufacturing methods include, for example, stacking the negative electrode and the positive electrode with a separator interposed therebetween, winding or folding the battery into a battery container, injecting the electrolyte into the container, and sealing it. The battery can be shaped appropriately, such as a coin, cylindrical, rectangular, or laminated battery.

[0180] The electrolyte may be in liquid or gel form. It is sufficient to select an electrolyte that effectively functions as a battery from among known electrolytes used in electrical storage devices, depending on the type of active material. The electrolyte may be a solution of an electrolyte dissolved in a suitable solvent. Examples of such electrolytes and solvents include compounds described in Japanese Patent No. 5999399 and the like.

[0181] The electrical storage device involved in this embodiment can be applied to lithium ion secondary batteries, electric double layer capacitors, lithium ion capacitors, etc. that need to be discharged at a high current density. Among these, lithium ion secondary batteries are particularly preferred. In the electrical storage device electrodes and electrical storage devices involved in this embodiment, components other than the electrical storage device binder composition can use known components for lithium ion secondary batteries, electric double layer capacitors, and lithium ion capacitors.

[0182] 5. Examples

[0183] The present invention will be described in detail below based on Examples, but the present invention is not limited to these Examples. "Parts" and "%" in Examples and Comparative Examples are based on mass unless otherwise specified.

[0184] 5.1. Examples 1 to 22, Comparative Examples 1 to 6

[0185] 5.1.1. Preparation of Binder Composition for Electrical Storage Devices

[0186] <Example 1>

[0187] A polymer (A1) dispersion was obtained by a one-stage polymerization as described below. To a reactor were added 500 parts by mass of water, a monomer mixture consisting of 1 part by mass of styrene, 5 parts by mass of acrylic acid, 64 parts by mass of 2-ethylhexyl acrylate, 25 parts by mass of acrylonitrile, and 5 parts by mass of isopropylmalononitrile, 1 part by mass of sodium dodecylbenzenesulfonate as an emulsifier, and 0.3 parts by mass of potassium persulfate as a polymerization initiator. Polymerization was carried out at a polymerization temperature of 75°C for 8 hours to obtain a polymer (A1) dispersion. The conversion rate of polymer (A1) at this time was 99%.

[0188] Next, 1 part by mass of 2,6-di-tert-butyl-p-cresol as an anti-aging agent was added, and a dispersion of polymer (A1) was added dropwise to 3000 parts by mass of a 0.5% calcium chloride aqueous solution. The obtained coagulant was washed with water, a portion of the obtained coagulant was dried at 80°C, and the amount of emulsifier contained in the coagulant was analyzed. Thereafter, the same operation was repeated, and when it was observed that the amount of emulsifier remaining in the coagulant no longer decreased, all the remaining coagulants were dried at 80°C and recovered. The amount of emulsifier contained in all the recovered coagulants was 7890 ppm relative to 100 parts by mass of polymer (A1). The method for determining the amount of emulsifier is as follows.

[0189] <Method for measuring emulsifier dosage>

[0190] After immersing 5 g of the dried coagulum in 100 mL of ethanol at room temperature for 1 hour, the extract is recovered. The extract is added to a pre-measured aluminum dish (X (g)). The solvent is completely removed using a hot air dryer. The dish is removed, cooled, and then weighed (Y (g)). The solid content concentration (A) is calculated from the weights X and Y measured in this manner using the following formula (2).

[0191] A(%)=((Y-X) / 5)×100·····(2)

[0192] Since the components included in the solid content concentration A are a mixture of the residual emulsifier and the antioxidant, the residual emulsifier amount is calculated using the following formula (3).

[0193] Residual emulsifier dosage (ppm) = ((100+1)×A(%)-1)×1000000

[0194] The polymer (A1) obtained above was added to N-methyl-2-pyrrolidone and stirred overnight to prepare a binder composition for a storage battery device in which the polymer (A1) was dissolved in N-methyl-2-pyrrolidone. The content of the polymer (A1) was adjusted to 8% by mass based on 100% by mass of the total binder composition for a storage battery device.

[0195] <Examples 2 to 22, Comparative Examples 1 to 6>

[0196] The types and amounts of monomers are shown in Tables 1 to 3 below, respectively. Other than that, each polymer was synthesized by one-stage polymerization in the same manner as in Example 1, and each binder composition for an electrical storage device was obtained in the same manner as in Example 1.

[0197] 5.1.2. Physical Property Evaluation of Binder Composition for Electrical Storage Devices

[0198] <Method for measuring polymerization conversion rate>

[0199] The polymerization conversion rate in the synthesis of each of the above-mentioned polymers was measured as follows.

[0200] The polymerization reaction solution is withdrawn at a predetermined time and placed in a pre-weighed aluminum dish (X (g)). The weight of the reaction solution is then measured (Y (g)). The mixture is dried at 155°C for 15 minutes using a hot air dryer. The aluminum dish is removed, cooled, and then the weight of the dish is measured (Z (g)). The polymerization conversion rate (%) is calculated from the weights X, Y, and Z thus measured according to the following formula (4).

[0201] Polymerization conversion rate (%) = ((Z-X) / Y) × 100 (4)

[0202] <Measurement of Weight Average Molecular Weight of THF-Soluble Component>

[0203] 10 mg of a storage device binder composition having a solid content concentration of 20% by mass was mixed with 5 mL of THF, allowed to stand at 25°C for 16 hours, and then passed through a 0.45 μm membrane filter to prepare a measurement sample. Next, the obtained measurement sample was used under the following measurement conditions to determine the weight average molecular weight (Mw) of the THF-soluble component in terms of polystyrene (RI detection) by gel permeation chromatography using the following column. The measurement results are shown in Tables 1 to 3 below.

[0204] [Measurement conditions]

[0205] Temperature: 35°C

[0206] Solvent: THF

[0207] Flow rate: 1.0 mL / min

[0208] Concentration: 0.2% by mass

[0209] ·Measurement sample injection volume: 100μL

[0210] [column]

[0211] · "GPC TSKgel α-2500" (30 cm x 2) manufactured by TOSOH Corporation was used. (Measurement was performed under the condition that the linear correlation equation of Log10 (Mw) - elution time was 0.98 or higher in the range of Mw 1,000 to 20,000,000.)

[0212] Evaluation of NMP solubility

[0213] The polymer dispersion obtained above was added to a calcium chloride aqueous solution, and a coagulated polymer was obtained through a water washing process and a drying process. N-methyl-2-pyrrolidone was added to dilute the obtained polymer to 1% by mass. The transparency of the 1% by mass NMP solution of the polymer thus obtained was confirmed by visual observation at 1 atmosphere and 23°C. The results are shown in Tables 1 to 3 below. If the 1% by mass NMP solution of the polymer is transparent, it is judged to be "dissolved" and expressed as "A". If the 1% by mass NMP solution of the polymer is translucent or turbid, it is judged to be "insoluble" and expressed as "B".

[0214] 5.1.3. Preparation of Lithium-ion Secondary Battery Cathode Slurry

[0215] In a twin-shaft planetary mixer (manufactured by PRIMIX Co., Ltd., trade name "TK HIVIS MIX 2P-03"), 37.5 parts by mass of a binder composition for a storage device (8% solid content conversion value, equivalent to 3 parts by mass based on the polymer obtained above) in which the polymer (A) is dissolved in NMP, 100 parts by mass of NMC622 (trade name "ME-8A", manufactured by Beijing Dangsheng Co., Ltd.) as a positive electrode active material, 5 parts by mass of acetylene black, and 74 parts by mass of NMP were added to prepare a slurry having a solid content concentration of approximately 50%, and stirred at 60 rpm for 1 hour.

[0216] After stirring for 1 hour to obtain a paste, the mixture was stirred and mixed at 200 rpm for 2 minutes and at 1800 rpm for 5 minutes using a stirring degassing machine (manufactured by THINKY Co., Ltd., trade name "Degassing Rentaro"), and further stirred and mixed under vacuum (about 5.0×10 3 Pa) and stirred and mixed at 1800 rpm for 1.5 minutes to prepare a slurry for a positive electrode of a lithium ion secondary battery.

[0217] 5.1.4. Fabrication and Physical Property Evaluation of Lithium-ion Secondary Battery Cathode

[0218] <Manufacturing of positive electrodes for lithium-ion secondary batteries>

[0219] The obtained lithium ion secondary battery positive electrode slurry was evenly coated on the surface of a 20 μm thick aluminum foil current collector using a doctor blade method so that the film thickness after drying was 100 μm, and dried at 120°C for 20 minutes. The density of the formed film (positive electrode active material layer) was then 3.0 g / cm 3 The positive electrode for lithium ion secondary battery was obtained by pressing the prepared product using a roller press.

[0220] <Evaluation of electrode status>

[0221] The lithium-ion secondary battery positive electrode obtained above was cut into 10 cm x 10 cm pieces, and the number of broken bubbles on its surface was visually counted. The evaluation criteria are as follows. The evaluation results are shown in Tables 1 to 3 below. Electrodes with no visible particle marks in the active material layer exhibited fewer coating defects caused by residual emulsifier and exhibited good cycle performance.

[0222] (Evaluation Criteria)

[0223] 5 points: If the number of particle marks due to broken bubbles is 0, there is no coating failure due to residual emulsifier, which is good.

[0224] 4 points: If the number of particle marks due to broken bubbles is 1 to 5, there is almost no coating failure due to residual emulsifier, which is good.

[0225] Point 3: If the number of broken bubble particle marks is 6 to 10, coating defects due to residual emulsifier are few and the result is good.

[0226] Point 2: If the number of broken bubble particle marks is 11 to 15, there will be some coating defects due to the residual emulsifier, making it difficult to use.

[0227] 1 point: If the number of broken bubble particle marks is 16 or more, coating defects due to residual emulsifier are frequent and the product cannot be used.

[0228] <Evaluation of Adhesion Strength>

[0229] On the surface of the positive electrode for lithium-ion secondary batteries obtained above, 10 cuts were made in the vertical and horizontal directions at 2 mm intervals from the active material layer to the depth of the current collector to make a checkerboard cut. An adhesive tape with a width of 18 mm (manufactured by NICHIBAN Co., Ltd., trade name "Cellotape" (registered trademark), specified in JIS Z1522:2009) was pasted on the cut and immediately peeled off. The degree of shedding of the active material was evaluated by visual judgment. The evaluation criteria are as follows. The evaluation results are shown in Tables 1 to 3 below.

[0230] (Evaluation Criteria)

[0231] 5 points: No active material layer was detached.

[0232] 4 points: 1 to 5 active material layers were detached.

[0233] 3 points: 6 to 20 active material layers were detached.

[0234] · 2 points: 21 to 40 active material layers were detached.

[0235] 1 point: 41 or more active material layers were fallen off.

[0236] 5.1.5. Fabrication and Physical Property Evaluation of Lithium-ion Secondary Batteries

[0237] <Preparation of negative electrode slurry for lithium-ion secondary batteries>

[0238] In a twin-shaft planetary mixer (manufactured by PRIMIX Co., Ltd., trade name "TK HIVIS MIX 2P-03"), 1 part by mass (solid content conversion) of a thickener (trade name "CMC2200", manufactured by Daicel Co., Ltd.), 100 parts by mass (solid content conversion) of graphite as a negative electrode active material, and 68 parts by mass of water were added and stirred at 60 rpm for 1 hour.

[0239] Next, SBR (trade name "TRD105A", manufactured by ENEOS Materials Co., Ltd.) was added in an amount equivalent to 2 parts by mass (based on solid content), and further stirred for 1 hour to obtain a paste. Water was added to the obtained paste to adjust the solid content to 50%, and then a stirring degasser (manufactured by THINKY Co., Ltd., trade name "Degas Rentaro") was used to stir and mix at 200 rpm for 2 minutes, at 1800 rpm for 5 minutes, and further at 1800 rpm for 1.5 minutes under vacuum to prepare a slurry for a negative electrode for a lithium ion secondary battery.

[0240] <Manufacturing of negative electrodes for lithium-ion secondary batteries>

[0241] The above-prepared lithium ion secondary battery negative electrode slurry was evenly coated on the surface of a 20 μm thick copper foil current collector using a doctor blade method in such a way that the film thickness after drying was 80 μm, and dried at 120°C for 20 minutes. The density of the film (negative electrode active material layer) was then 1.9 g / cm 3 The negative electrode for a lithium ion secondary battery was obtained by pressing the negative electrode using a roller press.

[0242] <Assembly of lithium-ion secondary batteries>

[0243] In a glove box replaced with Ar in a manner that the dew point becomes below -80°C, the negative electrode for the lithium ion secondary battery produced above is punched into a circle with a diameter of 16.16mm, which is placed on a 2-pole coin-type battery (manufactured by Hohsen Co., Ltd., trade name "HS Flat Cell"). Next, a separator (manufactured by Celgard Co., Ltd., trade name "Celgard#2400") made of a polypropylene porous membrane punched into a circle with a diameter of 24mm is placed on the negative electrode for the lithium ion secondary battery. After further injecting 500μL of electrolyte without introducing air, the positive electrode for the lithium ion secondary battery produced above is punched into a circle with a diameter of 15.95mm, and placed on the separator in an overlapping manner. The outer casing of the above-mentioned 2-pole coin-type battery is tightened and sealed with screws to assemble the lithium ion secondary battery. The electrolyte used here is a solution in which LiPF6 is dissolved at a concentration of 1 mol / L in a solvent of ethylene carbonate / ethyl methyl carbonate = 1 / 1 (mass ratio).

[0244] <Evaluation of resistance increase rate>

[0245] The lithium ion secondary battery produced above was charged at a constant current (1.0C) in a thermostat with a temperature adjustment of 25°C. When the voltage reached 4.25V, the charging was continued at a constant voltage (4.25V). The moment when the current value reached 0.01C was regarded as the end of charging (cut-off). Thereafter, discharge was started at a constant current (0.05C), and the moment when the voltage reached 2.5V was regarded as the end of discharge (cut-off). The discharge capacity of the 0th cycle was calculated. Charging was further started at a constant current (1.0C), and when the voltage reached 4.25V, the charging was continued at a constant voltage (4.25V). The moment when the current value reached 0.01C was regarded as the end of charging (cut-off). Thereafter, discharge was started at a constant current (1.0C), and the moment when the voltage reached 2.5V was regarded as the end of discharge (cut-off). The discharge capacity of the 1st cycle was calculated. This charge and discharge was repeated 100 times. After 100 cycles of charge and discharge, the battery was charged and discharged in the same manner as in the 0th cycle, and the 101st discharge capacity was evaluated. The resistance increase rate was calculated from the following formula (5) and evaluated according to the following criteria. The results are shown in Tables 1 to 3 below.

[0246] Resistance increase rate (%) = (discharge capacity at the 101st cycle - discharge capacity at the 100th cycle) / (discharge capacity at the 0th cycle - discharge capacity at the 1st cycle) × 100 (5)

[0247] (Evaluation Criteria)

[0248] 5 points: The resistance increase rate is 100% or more and less than 110%.

[0249] · Point 4: The resistance increase rate is 110% or more and less than 120%.

[0250] · Point 3: The resistance increase rate is 120% or more and less than 130%.

[0251] · Point 2: The resistance increase rate is 130% or more and less than 140%.

[0252] 1 point: The resistance increase rate is 140% or more and less than 150%.

[0253] 0 point: The resistance increase rate is 150% or more.

[0254] <Evaluation of cycle characteristics>

[0255] The lithium-ion secondary battery produced above was charged at a constant current (1.0C) in a thermostat with a temperature adjustment of 25°C. When the voltage reached 4.25V, the battery was charged at a constant voltage (4.25V). The moment when the current value reached 0.01C was regarded as the end of charging (cut-off). Thereafter, discharge was started at a constant current (1.0C), and the moment when the voltage reached 2.5V was regarded as the end of discharge (cut-off). The discharge capacity of the first cycle was calculated. This charge and discharge was repeated 100 times. The capacity retention rate was calculated by the following formula (6) and evaluated according to the following benchmarks. The results are shown in Tables 1 to 3 below.

[0256] Capacity retention (%) = (discharge capacity at the 100th cycle) / (discharge capacity at the 1st cycle) (6)

[0257] (Evaluation Criteria)

[0258] 5 points: Capacity retention rate is 95% or more.

[0259] · Point 4: Capacity retention rate is 90% or more and less than 95%.

[0260] · Point 3: Capacity retention rate is 85% or more and less than 90%.

[0261] · Point 2: The capacity retention rate is 80% or more and less than 85%.

[0262] 1 point: The capacity retention rate is 75% or more and less than 80%.

[0263] 0 points: Capacity retention rate is less than 75%.

[0264] 5.2. Examples 23 to 27, Comparative Examples 7 to 9

[0265] In Example 23, 12.5 parts by mass of a storage battery device binder composition containing the polymer (A6) synthesized in Example 6 (8 parts by mass in terms of solid content, equivalent to 1 part by mass based on the polymer (A6) obtained above) was used as the positive electrode binder, and NMP was added so that the solid content concentration of the lithium ion secondary battery positive electrode slurry became 70%. The same evaluation as in Example 6 was performed except that the compositions were used in the amounts of parts by mass described in Table 4 below.

[0266] In Comparative Example 7, 12.5 parts by mass of a storage battery device binder composition containing the polymer (B6) synthesized in Comparative Example 6 (8 parts by mass in terms of solid content, equivalent to 1 part by mass based on the polymer (B6) obtained above) was used as the positive electrode binder, and NMP was added so that the solid content concentration of the lithium ion secondary battery positive electrode slurry became 70%. The same evaluation as in Comparative Example 6 was performed except that the compositions were used in the amounts of parts by mass listed in the table.

[0267] 5.3. Examples 28 to 34

[0268] In Examples 28 to 34, the polymer (A6) synthesized in Example 6 was dissolved in the liquid medium (C) described in Table 5 below, and the same liquid medium (C) was used to prepare the slurry for the positive electrode of the lithium ion secondary battery. Except for this, the same evaluation as in Example 6 was performed.

[0269] 5.4. Evaluation results of examples and comparative examples

[0270] Tables 1 to 3 below show the polymer compositions, physical property measurement results, and evaluation results used in Examples 1 to 22 and Comparative Examples 1 to 6. Table 4 below shows the types of polymers used in Examples 23 to 27 and Comparative Examples 7 to 9 and the evaluation results. Table 5 below shows the types of liquid media used in Examples 28 to 34 and the evaluation results. The numerical values ​​representing polymer compositions shown in Tables 1 to 3 below represent parts by mass.

[0271]

[0272]

[0273]

[0274]

[0275]

[0276] The polymer numbers synthesized in each example are listed below the example numbers and comparative example numbers in Tables 1 to 3. The monomers, emulsifiers, and polymers in Tables 1 to 4 represent the following compounds, respectively.

[0277] <Single>

[0278] (Aromatic vinyl compound)

[0279] ·ST:Styrene

[0280] VT: Vinyltoluene

[0281] (Unsaturated carboxylic acid ester)

[0282] MMA: methyl methacrylate

[0283] TADB: dibutyl itaconate

[0284] TADM: dimethyl itaconate

[0285] TADE: diethyl itaconate

[0286] BA: Butyl acrylate

[0287] 2EHA: 2-ethylhexyl acrylate

[0288] HEMA: Hydroxyethyl methacrylate

[0289] ·CHMA: Cyclohexyl methacrylate

[0290] (Unsaturated carboxylic acid)

[0291] TA: Itaconic acid

[0292] TAMB: monobutyl itaconate

[0293] TAMM: Itaconate monomethyl ester

[0294] ·TAME:Itaconate monoethyl ester

[0295] AA: Acrylic acid

[0296] MAA: methacrylic acid

[0297] (α,β-unsaturated nitrile compound)

[0298] AN: Acrylonitrile

[0299] ·DMP: isopropylidenemalononitrile

[0300] ·FN:Fumaronitrile

[0301] ·TCE:Tetracyanoethylene

[0302] (sulfonic acid)

[0303] ·NaSS: sodium styrene sulfonate

[0304] VS: Vinyl sulfonic acid

[0305] ((Meth)acrylamide)

[0306] AAM: Acrylamide

[0307] MAM: methacrylamide

[0308] (vinyl pyrrolidone)

[0309] VP: N-vinyl-2-pyrrolidone

[0310] Emulsifier

[0311] (Sulfonic acid emulsifier)

[0312] ·Sodium alkane sulfonate: Trade name "LATEMUL PS", manufactured by Kao Corporation

[0313] Sodium alkyl diphenyl ether disulfonate: Trade name "PELEX SS-L", manufactured by Kao Corporation

[0314] ·Sodium dodecylbenzene sulfonate: Trade name "NEOPELEX G-65", manufactured by Kao Corporation

[0315] ·Sodium dialkyl sulfosuccinate: Trade name "PELEX TR", manufactured by Kao Corporation

[0316] (Carboxylic acid emulsifier)

[0317] Semi-solidified tallow fatty acid sodium soap: Trade name "NS Soap", manufactured by Kao Corporation

[0318] ·Potassium rosinate: Trade name "DIPROSIN A-100", manufactured by Toho Chemical Co., Ltd.

[0319] Polymers

[0320] PVdF: Trade name "HSV900", manufactured by Arkema, polyvinylidene fluoride

[0321] In Examples 1 to 22, as slurries for lithium-ion secondary battery electrodes, materials containing a binder composition for storage devices of the present invention and an active material were used. As a result, it was confirmed that the surface state of the active material layer formed by the slurry was good, and when the peel strength was measured, there was no brittleness of the active material layer itself, resulting in the shedding or cracking of the active material, and the binder obtained sufficient adhesion. In addition, it was confirmed that the rise in the internal resistance of the obtained lithium-ion secondary battery could be suppressed, and the cycle characteristics were also improved. Therefore, it can be seen that by using the binder composition for storage devices of the present invention, it is possible to produce electrodes for lithium-ion secondary batteries with excellent surface state, adhesion and ionic conductivity, and it is possible to improve the cycle characteristics of lithium-ion secondary batteries. In addition, according to Examples 23 to 34, it can be seen that even if the amount of binder, its type, and the type of liquid medium are changed, the effect will be shown.

[0322] The present invention is not limited to the above-mentioned embodiments and can be subjected to various modifications. The present invention includes a configuration that is substantially the same as the configuration described in the embodiments (for example, a configuration having the same function, method and result, or a configuration having the same purpose and effect). In addition, the present invention includes a configuration in which the non-essential parts of the configuration described in the above-mentioned embodiments are replaced with other configurations. In addition, the present invention also includes a configuration that can have the same effect as the configuration described in the above-mentioned embodiments or a configuration that can achieve the same purpose. Furthermore, the present invention also includes a configuration in which known technology is added to the configuration described in the above-mentioned embodiments.

Claims

1. A binder composition for an electrical storage device, comprising a polymer A and an emulsifier B, wherein the emulsifier B is present in an amount of 30 to 30,000 ppm relative to the total mass of the polymer A. Furthermore, when the total amount of repeating units contained in the polymer A is 100% by mass, the polymer A contains: 1 to 50% by mass of repeating units a1 derived from an aromatic vinyl compound, and 20 to 75% by mass of the repeating unit a2 derived from an unsaturated carboxylic acid ester.

2. The binder composition for an electrical storage device according to claim 1, wherein The polymer A further contains 0.5 to 10% by mass of a repeating unit a3 derived from an unsaturated carboxylic acid.

3. The binder composition for an electrical storage device according to claim 1 or 2, wherein The polymer A further contains 5 to 40% by mass of a repeating unit a4 derived from an α,β-unsaturated nitrile compound.

4. The binder composition for an electrical storage device according to claim 1 or 2, wherein The polymer A further contains 0.1 to 10% by mass of a repeating unit a5 derived from a compound having a sulfonic acid group.

5. The binder composition for an electrical storage device according to claim 1 or 2, wherein The polymer A further contains 0.1 to 10% by mass of a repeating unit a6 derived from (meth)acrylamide.

6. The binder composition for an electrical storage device according to claim 1 or 2, wherein The polymer A further contains 5 to 40% by mass of a repeating unit a7 derived from vinyl pyrrolidone.

7. The binder composition for an electrical storage device according to claim 1 or 2, wherein The solubility of the polymer A in N-methyl-2-pyrrolidone at 25° C. and 1 atm is 1 g or more per 100 g of N-methyl-2-pyrrolidone.

8. The binder composition for an electrical storage device according to claim 1 or 2, wherein The emulsifier B is an anionic surfactant.

9. The binder composition for an electrical storage device according to claim 1 or 2, wherein The liquid medium C is further contained. The liquid medium C is at least one selected from aliphatic hydrocarbons, alicyclic hydrocarbons, aromatic hydrocarbons, ketones, esters, ethers, glycol ethers, lactams, lactones, and amides. 10 . A slurry for electrical storage device electrodes, comprising the binder composition for electrical storage device according to claim 1 or 2 and an active material.

11. The slurry for electrical storage device electrodes according to claim 10, wherein The active material is a positive electrode active material. 12 . An electrical storage device electrode comprising a current collector and an active material layer, wherein the active material layer is formed by applying the slurry for an electrical storage device electrode according to claim 10 onto a surface of the current collector and drying the coating. 13 . An electric storage device comprising the electric storage device electrode according to claim 12 .

Citation Information

Patent Citations

  • Method of processing radioactive waste

    JP1984099399A

  • Binder for battery binder solution, electrode mixture, electrode structure and battery

    JP1998298386A

  • Binder composition for power storage device

    JP2019194944A